Information imperative in the development of the Commonwealth Caribbean. - Henry, Ralph M. (1991)
Analyses the relationship between information and economic performance in Commonwealth Caribbean countries and concludes that these countries have to develop a high level of information sensitivity among their populations in order to survive.